2019
DOI: 10.3904/kjim.2016.233
|View full text |Cite
|
Sign up to set email alerts
|

Higher glucagon-to-insulin ratio is associated with elevated glycated hemoglobin levels in type 2 diabetes patients

Abstract: Hyperglucagonemia relative to insulin could contribute to uncontrolled hyperglycemia in type 2 diabetes patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 42 publications
(46 reference statements)
6
18
0
Order By: Relevance
“…In this study, we demonstrated that both fasting and postprandial glucagon-C-peptide ratios were positively associated with HbA1c and postprandial glucose, and a high glucagon-C-peptide ratio might predict that the risk of poor glucose control increased significantly. A Korean study, similar to this study, demonstrated that a high postprandial GI ratio, rather than fasting GI ratio, was positively associated with uncontrolled hyperglucose in patients naive to insulin use [8] . The underlying mechanism by which the glucagon-C-peptide ratio can predict glucose control may be that the glucagon-C-peptide ratio reflects overall pancreatic islet dysfunction [10] .…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In this study, we demonstrated that both fasting and postprandial glucagon-C-peptide ratios were positively associated with HbA1c and postprandial glucose, and a high glucagon-C-peptide ratio might predict that the risk of poor glucose control increased significantly. A Korean study, similar to this study, demonstrated that a high postprandial GI ratio, rather than fasting GI ratio, was positively associated with uncontrolled hyperglucose in patients naive to insulin use [8] . The underlying mechanism by which the glucagon-C-peptide ratio can predict glucose control may be that the glucagon-C-peptide ratio reflects overall pancreatic islet dysfunction [10] .…”
Section: Discussionsupporting
confidence: 75%
“…Emerging data have shed light on the fact that the GI ratio is a determinate of hyperglycemia in patients with type 2 diabetes [7] . A Korean study including subjects native to insulin treatment demonstrated that a high postprandial GI ratio was positively associated with glycosylated hemoglobin A1c (HbA1c) [8] . Similarly, in patients with pancreatic cancer, a high GI ratio after a 75-g oral glucose challenge was a surrogate marker of uncontrolled hyperglycemia [9] .…”
mentioning
confidence: 99%
“…Consistent with a previous study, this study showed that higher postprandial GI ratio was positively correlated with HbA1c, FBG and HDL-C levels. 20,21 In patients with pancreatic cancer, GI ratio after a 75-g oral glucose challenge was independently correlated with HbA1c level. 22 In addition, appropriate choice of drugs for T2DM can be determined according to the glucagon response or change in absolute glucagon or GI ratio after glucose lowering drugs.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3]17 Previous studies have demonstrated that an increase in glucagon concentration and GI ratio reflects hyperglycaemia and degree of glycaemic control in individuals with T2DM. [18][19][20][21] Other studies have revealed a role of GI ratio in pancreatic cancer-related diabetes mellitus (DM). 22,23 Although glucagon relative to insulin is receiving much attention recently, there are little data regarding the association between GI ratio and NAFLD independent of insulin resistance in individuals with T2DM.…”
Section: Association Of Glucagon-to-insulin Ratio and Nonalcoholic Famentioning
confidence: 99%
“…Nevertheless, α-cells cannot be underestimated because their function to release glucagon and stimulate the liver to produce glucose [2]. Dysregulation of α-cells results in fasting and postprandial hyperglycemia in T2DM [3] and is accompanied by a higher glucagon-to-insulin ratio and augmentation of the pancreatic α-to β-cell area ratio [4,5]. In addition, there is also increased glucagon concentrations in prediabetes [6].…”
Section: Introductionmentioning
confidence: 99%